Biological characterization and genetic diversity of Fusarium spp. associated with yellowing disease in black pepper (Piper nigrum L.) in Malaysia - Shahnazi, Sahar (2012)
Yellowing disease or slow decline is one of the most important diseases of black pepper (Piper nigrum L.). To characterise the pathogen(s) responsible for yellowing disease of black pepper in Malaysia, 53 isolates of Fusarium were collected from the roots of diseased black pepper plants and from rhizosphere soils from major growing areas in Sarawak and Johor. 34 isolates of F. solani and 19 isolates of F. proliferatum were characterised and identified based on morphological characteristics and molecular techniques. DNA sequencing of the internal transcribed spacers (ITS1 and ITS2) and 5.8S ribosomal DNA (rDNA) regions was conducted to identify the Fusarium species. Nucleotide sequence analysis of the ITS regions revealed that this molecular technique enabled identification of Fusarium at the species level as F. solani and F. proliferatum. A pathogenicity test on three-month-old black pepper seedlings (cv. Kuching) demonstrated that F. solani is the dominant pathogen of the disease, whereas F. proliferatum is non-pathogenic. ISSR analysis and FAME profiles were used to examine genetic and biochemical relationships of Fusarium isolates. ISSR marker was used in the genetic diversity analysis of 34 F. solani isolates and 19 F. proliferatum isolates. Results indicate that there is a high level of genetic variation among the isolates of F. solani and also among the isolates of F. proliferatum. Among three populations of F. solani, population II (Sarikei) had the highest genetic diversity levels, whereas population III (Kulai) had the lowest genetic diversity levels. The low similarity index value between the two clusters of F. solani isolates showed the high genetic variability among the isolates. Fatty acid analysis was carried out to characterize, differentiate and determine biochemical relationships between and among F. solani and F. proliferatum isolates. Fatty acid analysis showed palmitic acid, stearic acid, oleic acid and linoleic acid were the most abundant fatty acids in these species. The most predominant fatty acid was linoleic acid (37.44 %) in F. solani and oleic acid (39.81%) in F. proliferatum. Our study suggests that fatty acid profiles have the potential to be used as a diagnostic tool for F. solani and F. proliferatum and isolates of these species could be characterized and differentiated at species levels. Both principal component analysis and cluster analysis showed clear biochemical relationships among isolates of these species. Some relationships between ISSR and FAME data were found. FAMEs data of Fusarium isolates supported ISSR findings. Both FAME and ISSR profiles can be used to study phenotypic and genetic diversity in Fusarium species and showed that there are some level of similarities between both techniques. The results of ISSR and FAME data showed that clusters were not related to geographic origin. The information obtained from FAME and ISSR data would help the breeder to develop resistant cultivars of black pepper, and also to assist in disease management.